Genetic and Non-genetic Workup for Pediatric Congenital Hearing Loss - Belcher, Ryan; Virgin, Frank; Duis, Jessica; Wootten, Christopher (Frontiers in Pediatrics, 2021)
Hearing loss is one of the most common concerns for presentation for a geneticist. Presentation prior to the age of one (congenital hearing loss), profound sensorineural hearing loss (SNHL), and bilateral hearing loss are sensitive and should raise concern for genetic causes of hearing loss and prompt referral for genetic testing. Genetic testing particularly in this instance offers the opportunity for anticipatory guidance including possible course of the hearing loss over time and also connection and evaluation for additional congenital anomalies that may be associated with an underlying syndrome versus isolated genetic hearing loss.